1977
DOI: 10.1007/bf01314847
|View full text |Cite
|
Sign up to set email alerts
|

Activation of latent herpesvirus hominis in explants of rabbit trigeminal ganglia: the influence of immune serum

Abstract: More than fifty albino rabbits were inoculated into the right scarified cornea with 10(7) PFU of the Kupka strain of human herpes virus type 1 (HHV-1). At intervals ranging from 4--280 days post infection (p.i.), both gasserian ganglia, both trigeminal nerve trunks and pieces from brain stem and from both corneas were explanted. Activation of the latent HHV-1 was found mainly in the homolateral ganglion tissue, but also in explants originating from the opposite ganglia. Within 24--72 hours, prior to the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is well known that latent HSV reactivates in cultured sensory ganglion fragments, which has been proven in mice as well as in rabbits [15,18,19]. Thus, explanted trigeminal ganglion fragments are suitable for studying various aspects of latency established in vivo, including the reactivation process [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that latent HSV reactivates in cultured sensory ganglion fragments, which has been proven in mice as well as in rabbits [15,18,19]. Thus, explanted trigeminal ganglion fragments are suitable for studying various aspects of latency established in vivo, including the reactivation process [20].…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA was prepared in a 20-Ìl reaction volume containing 0.5 Ìg of mRNA (20 Ìg/ml) or 1-1.5 Ìg of total RNA, 0.5 Ìg of oligo (dT) [12][13][14][15][16][17][18] primer (0.5 mg/ml) (Gibco), 10 mM of each dNTP (Perkin Elmer Cetus), 10 mM DTT (Gibco), 20 units of RNasin (Promega), 1! First Strand Buffer and 200 units of M-MLV reverse transcriptase (Gibco).This mixture was incubated at 37° for 60 min, and then at 95° for 5 min.…”
Section: Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our quantitative analysis indicates that stromal infiltration by chronic inflammatory cells largely of lymphocytes, with a few plasma cells is a n ubiquitous component of the human Gasserian ganglion at virtually any age (Table 1). Histological descriptions of the trigeminal ganglion in mice (Farkus-Bargeton et al, 1981), rats (Aldskogius & Arvidsson, 1978), rabbits (Rajcani et al, 1977;Rajcani & Ciampor, 1978) and macaque monkeys (Maxwell, Kruger & Pineda, 1969) have generally not recorded this feature, either spontaneously occurring or even following Herpes virus inoculation of the cornea.…”
Section: O N O N U C L E a R I N F I L T R A T E S A N D T H E P O mentioning
confidence: 99%
“…In ganglion cultures, the virus enters nerve cells or the end ofaxons in a different way from that in vivo. There have been many reports about ganglia inoculated z'n vivo with HSV stating that immune serum reduced the amount of free virus in the ganglion during the acute phase (11)(12)(13) or the latent phase of the infection (2,9,12) by the method of homogenisation or explantation. There may be a similar protective effect of the immune serum on ganglia inoculated in oioo or in tntro with HSV, Although Sekizawa et al showed that once latency is established antibody, is not necessary for its maintenance (14), we think that antibody is necessary for establishing the latent infection with the help of cell-mediated immunity, because it can prolong the survival time of ganglion nerve cells, but not eliminate the acute ganglionic infection completely, ships between HSV and ganglion cultures without the effect of cell-mediated immunity.…”
Section: Discussionmentioning
confidence: 99%